2003
DOI: 10.1080/15421400390213203
|View full text |Cite
|
Sign up to set email alerts
|

Organic Thin Film Photovoltaic Devices from Discotic Materials

Abstract: Since the {irst demonstration of organic photo voltaic devices much progress has been made. Organic solar cells reach now power conversion efficiencies of up to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…The UV/Vis spectrum of the series of 2,11-and 2,5-substituted FHBC-DOT compounds in dichloromethane solution (10 À5 m) are shown in Figure 2a and b. In both series of compounds in moving from zero thiophene units to three-thiophene dendron (3T) substituents, no redshift was observed either for the maximum absorption wavelength or the onset absorption wavelength.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The UV/Vis spectrum of the series of 2,11-and 2,5-substituted FHBC-DOT compounds in dichloromethane solution (10 À5 m) are shown in Figure 2a and b. In both series of compounds in moving from zero thiophene units to three-thiophene dendron (3T) substituents, no redshift was observed either for the maximum absorption wavelength or the onset absorption wavelength.…”
Section: Resultsmentioning
confidence: 93%
“…[8] There have only been limited reports on the use of HBCs in organic solar cells. [9][10][11][12] Recently, we reported the synthesis and optoelectronic properties of highly-soluble easily-functionalised HBC building blocks carrying conjugated substituents. [13] The primary challenge in the synthesis of these systems is the incorporation of conjugated substituents and alkyl groups for solubility.…”
mentioning
confidence: 99%
“…Later, they tried several other HBC-based DLCs (Figure 4) to prepare PV solar cells. 80,81 However, none of these devices could cross the PCE of the above-mentioned first device. PCE of some of the HBC-based DLCs used in PV solar cells are presented in Table 1.…”
Section: Hexabenzocoronene Dlcs In Pvsmentioning
confidence: 99%
“…82 Replacing the perylene dye 2a by other perylene dyes such as 2b-2d ( Figure 5) also did not improve the efficiency. 81,82 Jung et al 83 added a photoconducting carbazole-based polymer in the HBC/perylene solar cell to improve its efficiency. It was observed that the PCE of the device is dependent on the morphology of film.…”
Section: Hexabenzocoronene Dlcs In Pvsmentioning
confidence: 99%
See 1 more Smart Citation